Detector Simulation Challenges for Future Accelerator Experiments - Apostolakis, John; Bandieramonte, Marilena; Banerjee, Sunanda; Bartosik, Nazar; Corti, Gloria; Cosmo, Gabriele; Elvira, V. Daniel; Evans, Thomas; Gheata, Andrei; Pagan Griso, Simone; Ivantchenko, Vladimir; Jones, Christopher; et al. (Frontiers in Physics, 2022)
Detector simulation is a key component for studies on prospective future high-energy colliders, the design, optimization, testing and operation of particle physics experiments, and the analysis of the data collected to perform physics measurements. This review starts from the current state of the art technology applied to detector simulation in high-energy physics and elaborates on the evolution of software tools developed to address the challenges posed by future accelerator programs beyond the HL-LHC era, into the 2030-2050 period. New accelerator, detector, and computing technologies set the stage for an exercise in how detector simulation will serve the needs of the high-energy physics programs of the mid 21$^{st}$ century, and its potential impact on other research domains.